Biomechanical stability and stress distribution in intertrochanteric fracture of femur fixation by Titanium Alloy (Ti-6Al-4 V) nailing systems according to fracture reduction: A finite element analysis - Seong-Eun Byun; Il Won Suh; Soonchul Lee (Results in Engineering)
This study examines the biomechanical effectiveness of treating femoral intertrochanteric fractures using intramedullary nailing systems, assessing how stress distribution and displacement vary during walking and stair-climbing activities. Finite element analysis was employed to analyze different types of reductions, concentrating on anatomical, intramedullary, and extramedullary configurations, along with subtypes N, A, and P. The results indicated that anatomical reduction models, particularly subtypes N and A, consistently demonstrated better biomechanical stability, characterized by lower von Mises stress and enhanced load distribution. Conversely, intramedullary models, particularly subtype P, showed higher stress and displacement, which suggests greater risks for implant failure. These results offer important insights into factors reliant on the surgeon's technique, implying that refining reduction methods could significantly reduce stress and displacement during dynamic activities, thus lowering the likelihood of complications like implant failure.